1989
DOI: 10.1002/anie.198904481
|View full text |Cite
|
Sign up to set email alerts
|

New Intermediates in the Cyclocotrimerization of Thioxophosphorus(V) Cations with Alkynes

Abstract: A thiaphosphametallacyclopropane and a thiaphosphametallacycloheptadiene are important intermediates for understanding the mechanism of the cyclotrimerization of thioxophosphorus(V) cations and alkynes. These species are accessible by use of a bulky substituent R at the phosphorus atom. Compounds 2 are formed from the metallacyclopropane 1 and dimethyl or diethyl acetylenedicarboxylate in hexane. Upon heating in THF, they lose CO and are transformed into the known metallabicycloheptadienes 3. R1 = cyclohexyl; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The structure of the molecule of 2a (Figure ) contains a CpCr moiety bonded to two CO ligands and a η 2 -thiophosphinito ligand. This side-on mode of bonding has been structurally established for only a few complexes . The P−S bond distances in 2a , b (see Table ), slightly shorter than those in the literature examples, are intermediate between those of the typical PS (range 1.926(1)−1.966(2) Å) and the P−S (2.122(1) Å) single bond in such ligands …”
Section: Resultsmentioning
confidence: 65%
“…The structure of the molecule of 2a (Figure ) contains a CpCr moiety bonded to two CO ligands and a η 2 -thiophosphinito ligand. This side-on mode of bonding has been structurally established for only a few complexes . The P−S bond distances in 2a , b (see Table ), slightly shorter than those in the literature examples, are intermediate between those of the typical PS (range 1.926(1)−1.966(2) Å) and the P−S (2.122(1) Å) single bond in such ligands …”
Section: Resultsmentioning
confidence: 65%
“…The preceding structural and theoretical investigations have revealed that the negative charge of the species containing [R 2 PvE] − anions (E = O, S, Se, NR, etc.) routinely lies predominantly on E. [126][127][128][129][130] In this regard, Wright and co-workers showed that the oligomerisation of P 2 N 2 units can be achieved by the reaction of the deprotonated P(H)vO group with a P-Cl bond which probably proceeds through a change of the nucleophile center from phosphorus to oxygen, as shown in Scheme 20. 121 The first example of the crown-like phosphazane based macrocycle [{P(μ-N t Bu)} 2 (μ-O)] 4 (50), containing oxo-bridges was synthesized by condensing P 2 N 2 rings possessing P(H)vO and P-Cl moieties.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%